Integrative model of flexible management: a synergetic combination of scrum, bim, and lean approaches - SHCHERBAN, Bohdan (Ways to Improve Construction Efficiency, 2025)
The modern construction industry operates under constant change driven by digitalization, dynamic market processes, and increasing project complexity. Effective management in such an environment requires a shift from linear hierarchical systems to integrative models that combine flexibility, visual analytics, and lean production principles. The flexible integrative management model, built on the synergistic combination of SCRUM, BIM, and Lean approaches, provides a foundation for adaptive responses to the challenges of contemporary construction. It involves the interaction of three management levels: SCRUM – as a methodology for iterative planning and team collaboration; BIM – as a digital platform for coordination and data visualization; and Lean – as a concept of continuous improvement and waste elimination. This combination ensures a balance between decision-making speed, resource efficiency, and the quality of final results. The model is based on the principle of cyclical improvement: data obtained from the BIM platform are analyzed through the lens of Lean metrics and used to refine SCRUM iterations. This creates a continuous improvement loop where errors become an informational resource for development. The integrative system allows simultaneous control over time, cost, and quality indicators, forming an analytical basis for forecasting and risk management. In practice, such a model enhances project transparency, reduces conflicts, and accelerates managerial decision-making. The synergy of SCRUM, BIM, and Lean creates a collaborative decision-making environment where project participants interact through a unified digital model, and each team can respond promptly to changes. The integrative model not only eliminates duplication of functions but also fosters the emergence of new managerial roles – versatile professionals capable of combining technological, communicative, and analytical competencies. This forms the foundation for transitioning from fragmented structures to self-organizing teams and transforms project management into a continuous process of learning and adaptation. The integrative model of flexible management provides organizations with strategic stability and competitive advantage by enabling rapid adaptation to market changes, cost reduction, risk mitigation, and quality improvement. It represents not only a technological innovation but also a new managerial paradigm that unites flexibility, digital transparency, and system thinking in the field of construction management.